(untitled) (Dhaka University Journal of Biological Sciences, 2020)
The present study was conducted to investigate the suicidal ideation and attempts to suicide among the substance abusers. The study sample was comprised of 100 substance abusers (70 males and 30 females among them 18 were adolescent males, 7 were adolescent females, 52 were adult males and 23 were adult females) and selection was made by using purposive sampling technique. The instruments used for collecting data were: (1) Personal information questionnaire and (2) Bangla version of the Beck scale for suicide ideation. The data were analyzed by one-way ANOVA and independent sample t test. Results indicated that there were significant differences among the substance abuser’s suicidal ideation and suicide attempts. Yaba abusers had more suicidal ideation and took more suicide attempts than other substance abusers; adult abusers had more suicidal ideation and suicide attempts than adolescent abusers. Moreover, suicidal ideation was higher in males than females. Dhaka Univ. J. Biol. Sci. 29(2): 175-182, 2020 (July)